A Potential Cost of Long Genitalia in Male Guppies: the Effects of Current Speed on Reproductive Behaviour. (13th October 2016) - Kwan, Lucia; Dobkin, Adam N.; Rodd, F. Helen; Rowe, Locke
Abstract: In the fish family Poeciliidae, male genitalia, the gonopodia, are remarkably diverse across species; however, we still do not have a good understanding of the evolutionary processes promoting this diversity. For one trait, gonopodium length, several studies support a role for sexual conflict in selection for longer gonopodia. However, genital elongation may come at a cost of reduced locomotor abilities (e.g. resulting from greater drag and resistance). In this study, we were interested in the potential role of natural selection on the evolution of gonopodium length in poeciliids. Specifically, we asked whether a greater genital length impedes male reproductive behaviours at higher flow rates in the Trinidadian guppy, Poecilia reticulata . Using a flow chamber, males were placed with females in low‐ and high‐flow regimes and reproductive behaviours were measured. We did not find evidence for a cost of bearing a longer gonopodium at high flow. However, males did alter their mating tactics in response to current flow. We discuss the implications of our findings, in the light of habitat selection, on the forms of selection operating on gonopodium length and the mating interactions between the sexes in poeciliids.